Integrating Islamic Principles into Ethical Decision-Making Education for Maritime Cadets - Cahyadi, Tri; Purnama, Chanra; Hutagaol, Meilinasari Nurhasanah; Mudakir; Ahmadi, Pesta Veri (Universitas Islam Negeri Raden Intan Lampung, 2025)
Ethical decision-making is vital in maritime operations, where actions impact safety, sustainability, and professionalism. Islamic principles, grounded in integrity, responsibility, and justice, offer a culturally relevant foundation for ethical education in maritime training. However, their systematic integration into cadet curricula has not been extensively explored. This research addresses this gap by aligning Islamic principles with practical ethical training, employing case-based learning as a pedagogical tool. The study focuses on how Islamic values and case-based learning can foster ethical competence, critical thinking, and professional readiness among first-semester cadets. Using a qualitative approach, data were collected through semi-structured interviews, surveys, and classroom observations involving 15 experienced maritime lecturers. Thematic analysis was conducted to assess cadets’ development in ethical decision-making, evaluate the effectiveness of case-based learning, and identify integration challenges. The results reveal that integrating Islamic principles significantly enhanced cadets’ ability to analyze scenarios, identify ethical dilemmas, and propose solutions aligned with these values. However, challenges such as variability in cadets’ prior ethical knowledge and the lack of culturally relevant case studies were identified. This research provides a practical framework for ethical education in maritime training, highlighting the importance of culturally aligned curricula and experiential learning. The study contributes to preparing cadets for ethical and professional challenges in global maritime contexts.